Prediction of Sinensetin from Kumis Kucing (Orthosiphon aristatus) as Aspulvinone Dimethylallyltransferase Inhibitor for Anticancer Agent - Prasetyawan, Fendy; Arifin, Chandra; Astutik, Widhi; Rohmah, Eka Hayati; Kadir, Mujtahid Bin Abd; Ariawan, M Wahyu; Marhenta, Yogi Bhakti; Mildawati, Ratna; Saristiana, Yuneka; Rofiq, Abd (Marasofi International Media and Publishing (MIMP), 2025)
Sinensetin, a polymethoxylated flavone found in Orthosiphon aristatus (commonly known as Kumis Kucing), was evaluated in silico for its potential inhibitory activity against Aspulvinone Dimethylallyltransferase, an enzyme implicated in cancer-related biosynthetic pathways. The SMILES structure of sinensetin was retrieved from PubChem and analyzed using the PASS online prediction tool (www.way2drug.com). The results showed a high probability of activity (Pa = 0.865) and a very low probability of inactivity (Pi = 0.016), indicating that sinensetin is likely to act as a potent inhibitor of the enzyme. These findings suggest that sinensetin could be a promising anticancer agent candidate by targeting Aspulvinone Dimethylallyltransferase. Further studies are recommended to validate this prediction through molecular docking and biological assays.